RELATIONSHIP BETWEEN PROLACTIN HORMONE LEVEL, MOLTING AND DUCK EGG PRODUCTION - Susanti, T.; Noor, R.R.; Hardjosworo, P.S.; Prasetyo, L.H. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
The aims of this study were to obtain information on the mechanism of molting and the prolactinhormone levels affecting egg production. The study utilized AP (crossbred of Alabio ♂ with Peking ♀)and PA (crossbred of Peking ♂ and Alabio ♀ ducks) with a total of 180 birds. The observed variableswere the duration of cessation of egg production before and after molting, the prolactin hormone level inthe period of molting, the egg production period before and after molting. The data was analyzed usingANOVA, regression and correlation. The results showed that AP crossbred had fewer molting (23.33%)compared to PA (50.00%). The mechanism of molting is always preceded by cessation of eggproduction, molting and relaying. The prolactin hormone concentrations of AP and PA in the periodbefore and after molting were significantly higher than in the period of molting. At the egg productionperiod before molting, the prolactin hormone concentration of AP ducks was higher than the PA ducks.So that the egg production of AP before molting (0-16 weeks) was higher than the PA. The eggproduction of AP was higher than PA, 256.66±6.00 vs 232.22±6.64 eggs for 48 weeks. So it can beconcluded that the prolactin hormone affects the molting and egg production.